Aberrant activation of TGF-β1 induces high bone turnover via Rho GTPases-mediated cytoskeletal remodeling in Camurati-Engelmann disease - Chen, Qi; Yao, Yan; Chen, Kun; Chen, Xihui; Li, Bowen; Li, Rui; Mo, Lidangzhi; Hu, Weihong; Zhang, Mengjie; Wang, Zhen; Wu, Yaoping; Wu, Yuanming; et al. (Frontiers in Endocrinology, 2022)
In the adult skeleton, the bone remodeling process involves a dynamic coordination between osteoblasts and osteoclasts, which is disrupted in diseases with high bone turnover rates and dysregulated transforming growth factor beta 1 (TGF-β1). However, little is known about how TGF-β1 signaling mediates bone resorption. Here, we described a pedigree with a heterozygous variant in TGF-β1 (R218C) that resulted in aberrant activation of TGF-β1 through an activating mechanism that caused Camurati-Engelmann disease (CED). We showed that CED patients have high levels of active Rho GTPases and the migration-related proteins Integrin β1 and Integrin β3 in their peripheral blood. HEK293T cells transfected with a plasmid encoding this mutant expressed high levels of TGF-β1 and active Rho GTPases. Furthermore, activation of Rho by TGF-β1 increased osteoclast formation and bone resorption, with increased migration of pre-osteoclasts, as well as cytoskeletal remodeling of pre-osteoclasts and mature osteoclasts. Importantly, pharmacological inhibition of Rho GTPases effectively rescued hyperactive TGF-β1-induced osteoclastogenesis in vitro. Overall, we propose that Rho GTPases mediate TGF-β1-induced osteoclastogenesis and suggest that Rho-TGF-β1 crosstalk is associated with high bone turnover in CED.